SULUAH DALAM NAGARI; PENCIPTAAN KRIYA EKSPRESI DENGAN INSPIRASI BUNDO KANDUANG - Fera wati; Lisa Dewi (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2020)
Bundo Kanduang, in essence, is personally values of a mother with a very noble position in Minangkabaunese society which are embraced by showing good character and being role model, representative, and light for the family and society. In this circumstance, Bundo Kanduang becomes an inspiration for the creation of leather crafts in the form of decorative lights which has a called Suluah. The concept of personal expression underlies this creation that is presented through three components such as the theme, visual and meaninng associated with the work. The process is done through methods and stages in the form of exploration, source, idea, design, and embodiment which is done by craftmanship as a basis for working on the art of crafts. ABSTRAKBundo Kanduang pada hakikatnya merupakan nilai-nilai kepribadian seorang ibu dengan kedudukan sangat mulia dalam masyarakat Minangkabau dengan budi, serta kemampuan menjadi contoh, teladan serta penerang bagi kaum, dan masyarakat. Dalam hal ini Bundo Kanduang menjadi inspirasi penciptaan karya kriya kulit berupa lampu hias yang diwujudkan dengan tema suluah. Konsep ekspresi personal melandasi penciptaan karya yang dihadirkan melalui tiga komponen berupa tema, wujud visual, serta makna yang terkandung dalam karya. Prosesnya dilakukan melalui metode dan tahapan berupa eksplorasi sumber ide, perancangan, dan perwujudan yang dilakukan dengan craftmanships sebagai landasan garap dalam seni kriya.Kata Kunci: Suluah, Bundo Kanduang, kriya kulit.